IMPLEMENTATION OF THINK-PAIR-SHARE MODEL TO INCREASE THE SIXTH-GRADE STUDENTS’ LEARNING ACTIVITIES AND OUTCOMES AT SD NEGERI 4 PANARUNG - Arini Arta Naibaho; Theo Jhoni Hartanto; Pri Ariadi Cahya Dinata; Risnameli (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The lack of students’ learning activities and outcomes in class VI-B at SDN 4 Panarung is based on the teacher-dominated learning and lecture method. To overcome the problem, the classroom action research through the Think-Pair-Share model was applied to the students. This paper reports the improvement of the student’s learning activities and outcomes on the theme of "Menjelajah Angkasa Luar” (Exploring Outer Space) and the subtheme of "Keteraturan Yang Menakjubkan” (Amazing Order) by applying a cooperative learning model, TPS. There are three classroom action research cycles applied to 16 sixth-grade students in which each cycle contains planning, action, observation, and reflection. The data analysis technique of the research used was descriptive, which compares the test value of each cycle with the success indicators. The research results indicate that (1) the average score of student activity in cycle I was 69, in cycle II it was 76.53, and in cycle III it was 90.53 and (2) the average score of student learning outcomes in cycle I was 65.63, in cycle II it was 74.67, and cycle III it was 82.14. It can be inferred that the implementation of the Think-Pair-Share model can improve student learning activities and outcomes in the theme of "Menjelajah Angkasa Luar” (Exploring Outer Space) and the subtheme of "Keteraturan Yang Menakjubkan” (Amazing Order).